The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1747954117739548
|View full text |Cite
|
Sign up to set email alerts
|

Behind closed doors: The role of debriefing and feedback in a professional rugby team

Abstract: Despite the popularity of performance analysis with high performance rugby environments, limited attention has been paid to understanding how coaches and practitioners use this information to impact on performance. The aim of this case study was to gain an in-depth understanding of how a professional rugby team-playing in New Zealand's ITM cup competition-uses the post-match and pre-match meetings to debrief after performance and preview prior to future performance. Multiple ethnographic techniques were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…According to both the athletes and staff, the use of PA directly contributed to the development of positive culture and brought athletes and staff together. These findings are in contrast to the views of male New Zealand rugby players, where the team's coaches attempted to create an active process to encourage self-learning and selfdiscovery (Middlemas, Croft, & Watson, 2017). Instead, certain players never took part in discussions causing others to perceive this negatively impacted on the team's performance.…”
Section: Introductioncontrasting
confidence: 76%
“…According to both the athletes and staff, the use of PA directly contributed to the development of positive culture and brought athletes and staff together. These findings are in contrast to the views of male New Zealand rugby players, where the team's coaches attempted to create an active process to encourage self-learning and selfdiscovery (Middlemas, Croft, & Watson, 2017). Instead, certain players never took part in discussions causing others to perceive this negatively impacted on the team's performance.…”
Section: Introductioncontrasting
confidence: 76%
“…Information was presented to players in two separate meetings each week. Specifically, at a post-match meeting held on Monday and a pre-match meeting held on Thursday (Middlemas et al, 2018 ). The purpose of the post-match meeting was to analyze the scout reports related to the team itself and to visualise, using video clips, the negative and positive aspects of their game.…”
Section: Methodsmentioning
confidence: 99%
“…It is also transmitted to athletes (Wright et al, 2016 ). Currently, because it is vital to involve players in the pursuit of sports performance (Bampouras et al, 2012 ; Middlemas et al, 2018 ), high-level sports teams typically incorporate meetings into their training schedules in order to present information to their players (Groom and Cushion, 2004 ; Mesquita et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Middlemas et al (2017) identified only limited information (< 20%) generated by the performance analysis process was incorporated into the player's formal feedback sessions. This may appear concerning to the applied practitioner due to the large amount of work undertaken yet ultimately absent within feedback.…”
Section: Feedback Timescale Session Length and Session Balancementioning
confidence: 99%
“…However, despite their critical role in the feedback process, the views of these coaches have been rarely reported within academic writing to date. Many of the studies investigating coach, analyst, or athlete perceptions have primarily focused on larger-team based sports such as rugby union (Francis & Jones, 2014;Kraak, Magwa & Terblanche, 2018;Middlemas, Croft & Watson, 2017;Painczyk, Hendricks & Kraak, 2017) and football (Groom & Cushion, 2004;Groom & Cushion, 2005;Reeves & Roberts, 2013;Wright, Atkins, Jones & Todd, 2013). However, some studies have also incorporated multi-sport (Bampouras, Cronin & Miller, 2012;Martin et al, 2018;Wright, Atkins & Jones, 2012) and individual-sport (Butterworth, Turner & Johnstone, 2012;Mooney et al, 2016) demographics, thus providing a wider insight into the perceptions and utilisation of performance analysis within applied practice.…”
Section: Introductionmentioning
confidence: 99%